Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Characterisation of LV myocardial exercise function by 2-D strain deformation imaging in elite adolescent footballers - Guido E. Pieles; Lucy Gowing; Diane Ryding; Dave Perry; Steven R. McNally; A. Graham Stuart; Craig A. Williams (European Journal of Applied Physiology, 2021)
Purpose Few data exist on the descriptions of LV myocardial mechanics and reserve during dynamic exercise of adolescent athletes. The aim of this study was to describe the LV myocardial and cardiopulmonary changes during exercise using 2-D strain deformation imaging. Methods Elite adolescent male football players ( n = 42) completed simultaneous cardiopulmonary exercise testing (CPET) and exercise echocardiography measurement of LV myocardial deformation by 2-D strain imaging. LV longitudinal and circumferential 2-D strain and strain rates were analyzed at each stage during incremental exercise to a work rate of 150 W. Additionally, exercise LV myocardial deformation and its relation to metabolic exercise parameters were evaluated at each exercise stage and in recovery using repeated measures ANOVA, linear regression and paired t tests. Results LV peak systolic baseline 2-D strain (longitudinal: − 15.4 ± 2.5%, circumferential: − 22.5 ± 3.1%) increased with each exercise stage, but longitudinal strain plateaued at 50 W (mean strain reserve − 7.8 ± 3.0) and did not significantly increase compared to subsequent exercise stages ( P > 0.05), whilst circumferential strain (mean strain reserve − 11.6 ± 3.3) significantly increased ( P < 0.05) throughout exercise up to 150 W as the dominant mechanism of exercise LV contractility increase. Regression analyses showed LV myocardial strain increased linearly relative to HR, VO 2 and O 2 pulse ( P < 0.05) for circumferential deformation, but showed attenuation for longitudinal deformation. Conclusion This study describes LV myocardial deformation dynamics by 2-D strain and provides reference values for LV myocardial strain and strain rate during exercise in adolescent footballers. It found important differences between LV longitudinal and circumferential myocardial mechanics during exercise and introduces a methodology that can be used to quantify LV function and cardiac reserve during exercise in adolescent athletes.

Site use and connectivity of female grey seals (Halichoerus grypus) around Wales - Izzy Langley; Tobias Rosas da Costa Oliver; Lex Hiby; Thomas B. Stringell; Ceri W. Morris; Oliver O’Cadhla; Lisa Morgan; Kate Lock; Sarah Perry; Stephen Westcott; Dave Boyle; Birgitta I. Büche; et al. (Marine Biology, 2020)
Grey seals ( Halichoerus grypus ) are a qualifying feature of three special areas of conservation (SACs) in Wales, yet relatively little is known of their site use along this coastline. Since 1992, many individuals and organisations have contributed to a grey seal photographic identification database held by Natural Resources Wales, which is one of the largest and oldest of its kind, providing key information from grey seal haul-out sites around the Celtic and Irish Seas. Here, we investigated spatial connectivity of haul-out sites and fidelity of adult females to breeding sites. The minimum number of adult female grey seals using the area between 1992 and 2016 was 2688. Individual capture histories and relative spatial transition probabilities ( P ij ) between pairs of location groups were calculated. Adjacent locations were highly connected (e.g. Lleyn Peninsula and Bardsey, P ij = 0.7) but connections spanned the entire region, up to 230 km apart (e.g. Skomer and Dee Estuary, P ij = 0.004). Resights were recorded within SACs (e.g. Lleyn Peninsula and Bardsey [Lleyn Peninsula and the Sarnau SAC], P ij = 0.7), between SACs (e.g. Bardsey and Skomer [Pembrokeshire Marine], P ij = 0.03), between SACs and non-designated areas (e.g. Skerries and Bardsey, P ij = 0.09) and between sites outside any protected area (e.g. Dee Estuary and Anglesey, P ij = 0.5). While inter-annual fidelity to breeding sites was high ( P ij = 0.82–1), individual female grey seals moved throughout the region. This evidence of extensive site use beyond protected areas is important for the management and conservation of grey seals around Wales.

Recurrent Hypoglycemia Exacerbates Cerebral Ischemic Damage in Diabetic Rats via Enhanced Post-Ischemic Mitochondrial Dysfunction - Vibha Shukla; Perry Fuchs; Allen Liu; Charles H. Cohan; Chuanhui Dong; Clinton B. Wright; Miguel A. Perez-Pinzon; Kunjan R. Dave (Translational Stroke Research, 2019)

First global molecular phylogeny and biogeographical analysis of two arachnid orders (Schizomida and Uropygi) supports a tropical Pangean origin and mid‐Cretaceous diversification - Ronald M. Clouse; Michael G. Branstetter; Perry Buenavente; Louise M. Crowley; Jesse Czekanski‐Moir; David Emmanuel M. General; Gonzalo Giribet; Mark S. Harvey; Daniel A. Janies; Alma B. Mohagan; Dave P. Mohagan; Prashant P. Sharma; et al. (Journal of Biogeography, 2017)
Aim We sought to illuminate the history of the arachnid orders Schizomida and Uropygi, neither of which have previously been subjected to global molecular phylogenetic and biogeographical analyses. Location Specimens used in this study were collected in all major tropical and subtropical areas where they are presently found, including the Americas, Africa, Australia and the Indo‐Pacific region. Methods From field‐collected specimens, we sequenced two nuclear and two mitochondrial markers, combined these with publicly available data, and conducted multi‐gene phylogenetic analyses on 240 Schizomida, 24 Uropygi and 12 other arachnid outgroups. Schizomid specimens included one specimen from the small family Protoschizomidae; other schizomid specimens were in Hubbardiidae, subfamily Hubbardiinae, which holds 289 of the order's 305 named species. We inferred ancestral areas using the Dispersal‐Extinction‐Cladogenesis model of range evolution, and we used fossil calibrations to estimate divergence times. Results We recovered monophyletic Schizomida and Uropygi as each other's sister group, forming the clade Thelyphonida, and terminals from the New World were usually positioned as the earliest diverging lineages. The ancestral area for schizomids reconstructed unambiguously to the region comprised of Mexico, Southern California and Florida (the xeric New World subtropics). Optimal trees suggested a single colonization of the Indo‐Pacific in both orders, although this did not receive bootstrap support. Molecular dating gave an Upper Carboniferous origin for each order, and a mid‐Cretaceous expansion of Schizomida, including the origin and initial diversification of those in the Indo‐Pacific. Main conclusions Ancestral area reconstructions, molecular dating and fossil evidence all support an Upper Carboniferous, tropical Pangean origin for Thelyphonida, Schizomida and perhaps Uropygi. Much of this region became unsuitable habitat for these arachnids during the breakup of Pangea, but they persisted in the area that is now Meso‐ and South America. From there they then expanded to the Indo‐Pacific, where schizomids today display an idiosyncratic combination of microendemism and long‐range dispersal.

Explaining fire‐driven landscape transformation during the Initial Burning Period of N ew Z ealand's prehistory - George L. W. Perry; Janet M. Wilmshurst; Matt S. McGlone; Dave B. McWethy; Cathy Whitlock (Global Change Biology, 2012)
At the time of M āori settlement, ca. 750 years ago, N ew Z ealand's ecosystems experienced catastrophic change, including the introduction of fire to ignition‐limited ecosystems and the resulting widespread loss of forest. While high‐resolution sediment‐charcoal analyses suggest this forest loss was rapid, M āori populations were small and transient during the Initial Burning Period and there is evidence for widespread fire activity in places where there is little archaeological evidence of human presence. These observations beg the question ‘how did small populations manage to transform large areas so rapidly?’ Using a simulation model, we demonstrate how the relationship between time since fire and flammability in N ew Z ealand's forests drives positive feedbacks that allow for rapid and extensive deforestation. Under ignition scenarios mirroring prehuman conditions, the model did not produce significant deforestation – thus, it is extremely unlikely that deforestation could have occurred without human‐initiated burning. Scenarios where ignition was spatio‐temporally random also failed to result in deforestation. Rapid and widespread forest loss occurred in scenarios incorporating spatio‐temporally savvy selection of ignition locations. Targeting ignitions in flammable vegetation was more important than targeting ignitions in years with favourable climatic conditions. However, targeting in space and time concurrently, such that flammable vegetation was ignited during favourable climatic years was the most efficient strategy of those simulated. Following the Initial Burning Period decadal ignitions would have been sufficient to maintain a deforested shrubland/grassland landscape. New Z ealand's Initial Burning Period is one of many that occurred across eastern Polynesia following human settlement, and these events have left long‐term legacy effects that remain evident in contemporary landscapes. Improving understanding of how humans shaped environments in N ew Z ealand in the past has implications for eastern P olynesia as a whole.

Topically applied myco-acaricides for the control of cattle ticks: overcoming the challenges - Perry Polar; Dave Moore; Moses T. K. Kairo; Adash Ramsubhag (Experimental and Applied Acarology, 2008)

Comparison of Water, Oils and Emulsifiable Adjuvant Oils as Formulating Agents for Metarhizium Anisopliae for Use in Control of Boophilus Microplus - Perry Polar; Moses T.K. Kairo; Dave Moore; Rupert Pegram; Sally-Ann John (Mycopathologia, 2005)